Responding to crises in the African Great Lakes - Evans, Glynne; International Institute for Strategic Studies (Oxford [England] ; New York : Oxford University Press for the International Institute for Strategic Studies, 1997)
This paper examines the international responses to the ethnic conflicts in Burundi and Rwanda from 1993-97 and their overspill into Zaire (now the Democratic Republic of Congo). The author concludes that the international response was impotent and incoherent. Soundbite diplomacy led decision-makers to act before adequately assessing the situation. In the end, it was the power of local rather than international intervention that set the agenda and provided the solution. The author urges a number of changes in response by the international community: the UN should create a Conflict Analysis Centre at its headquarters in New York; governments need to promote lateral understanding and cooperation between different players, including the media and the non-governmental organisation community; enlightened outside support can be the most valuable when an inexperienced government has just taken over; and greater understanding is needed on the part of Western states that traditional Western patterns of diplomacy are often inappropriate in other regions. Instead, non-party democracy and a strong element of sub-regional cooperation may be the models for the future.
Identity and security -- External military intervention versus local action.
Item is bound in Adelphi papers 1997.
Includes bibliographical references (pages 87-96).
Keywords: United Nations -- Armed Forces -- Burundi -- History -- 20th century; United Nations; UN; Organization for Security and Co-operation in Europe; UN High Commissioner for Refugees; 1900-1999; Hutu (African people) -- Burundi -- Politics and government; Tutsi (African people) -- Burundi -- Politics and government; Genocide -- Prevention; Genocide -- Rwanda; Genocide -- Burundi; Intervention (International law); Intervention (Droit international); Armed Forces; Ethnic relations -- Political aspects; Genocide; Genocide -- Prevention; Hutu (African people) -- Politics and government; Intervention (International law); Politics and government; Tutsi (African people) -- Politics and government; Ethnicity -- Africa, Central; ARMED CONFLICTS; HUMANITARIAN INTERVENTION; DISPUTE SETTLEMENT; CONFLICT MANAGEMENT; BURUNDI; DEMOCRATIC REPUBLIC OF THE CONGO; RWANDA; GREAT LAKES REGION (AFRICA); PEACEKEEPING OPERATIONS; NON-GOVERNMENTAL ORGANIZATIONS; INTERGOVERNMENTAL ORGANIZATIONS; Burundi -- Politics and government -- 20th century; Burundi -- Ethnic relations -- Political aspects -- History -- 20th century; Rwanda -- History -- Civil War, 1994.; Burundi -- Politics and government; Rwanda -- Politics and government; Burundi; Ruanda; Africa, Central -- Ethnic relations; Rwanda -- Ethnic relations; Burundi -- Ethnic relations; Congo (Democratic Republic) -- Ethnic relations; Kongo <Demokratische Republik>; Ethnic conflicts; Political science; Sociology; History